Investigation of antioxidant & cytotoxic properties of callicarpa attenuata - Aziz, Shah Md. Mahathir (BRAC University, 2018)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2017.